Information technology in the age of emergency public health response. - Popovich, M.L.
For over 20 years, our nation's public health system has continually struggled to combat ongoing and emerging public health threats and emergencies. Deadly threats have created considerable interest among healthcare providers, public health officials, state and local politicians, the Congress, and the President. As a consequence, substantial funding has been made available to federal, state, and local public health agencies to build a stronger, more vigilant public health system. Significant investment is being made to develop local and regional public health response plans, create robust information systems to support exchange of critical data and information, improve workforce competencies, and enhance communication systems needed to inform responders, the healthcare community, and the public. To succeed, public health agencies need a sophisticated and proven information technology framework that can be effectively applied to improve public health readiness. This article provides insight into the development of that framework, an integrated disease surveillance system for rapid detection, tracking, and managing of public health threats, within the context of the overall public health system
Keywords: Congress; President; Communication systems; Critical data; Emergencies; Emergency public health response; Federal public health agencies; Healthcare providers; Information technology; Integrated disease surveillance system; Local politicians; Local public health agencies; Managing; Public health officials; Public health response plans; Public health threats; Rapid detection; Responders; Robust information systems; State politicians; State public health agencies; Substantial funding; Tracking; Workforce competencies